The Ruling on Killing Sick and Endangered Animals - Mustafa Ahmed Habib (Islamic Sciences Journal, 2025)
The research entitled “The Ruling on Killing Sick and Endangered Animals” examines the jurisprudential foundations related to the permissibility of killing animals suffering from incurable diseases, as well as those carrying contagious illnesses that may pose a threat to human health. The study highlights the emphasis placed by Islamic law on the protection and humane treatment of animals due to their essential role in sustaining ecological balance. Accordingly, the killing of endangered species is strictly prohibited, as their preservation is a legal and ethical obligation aimed at preventing the loss of biodiversity and ensuring environmental stability.